(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Post-Traumatic Stress Disorder (PTSD) is a severe psychological condition resulting from experiencing or witnessing traumatic events involving threats to life, health, or personal integrity. In recent years, the demand for psychotherapeutic support for PTSD has increased significantly, particularly among veterans, victims of violence, accidents, disasters, and forced migration. In this context, integrative psychotherapy approaches, which combine elements from various schools, have gained importance